Genesis of the Formation of Philosophical and Historical Roots of Islamic Bioetics - Umirzakova Nargiza Akmalovna (European Journal of Life Safety and Stability (2660-9630), 2024)
In Uzbekistan, bioethics is developing effectively as a new, separate field of science. In this article, the author explores the formation and historical genesis of the philosophical roots of bioethics that appeared in the East. In the article, the author conducts a philosophical analysis of the teachings of Muslim bioethics, according to which questions about the essence of health and illness, body and soul, life and death were key and represented a single whole. Based on their essence, we can believe that it is necessary to cultivate professional ethics in future doctors, at the center of which are such positive qualities as compassion, respect for human dignity, reverence for life and willingness to help the patient.